Rational Cubic Spline Interpolation for Monotonic Interpolating Curve with C2 Continuity - Bin Abdul Karim, S.A. (EDP Sciences, 2017)
Monotonicity preserving interpolation is very important in many sciences and engineering based problems. This paper discuss the monotonicity preserving interpolation for monotone data set by using C2 rational cubic spline interpolant (cubic/quadratic) with three parameters. The data dependent sufficient conditions for the monotonicity are derived with two degree freedom. Numerical results suggests that the proposed C2 rational cubic spline preserves the monotonicity of the data and outperform the performance of the other rational cubic spline schemes in term of visually pleasing. © The authors, published by EDP Sciences, 2017.